PENINGKATAN MINAT BELAJAR IPA MELALUI MEDIA GAMBAR PADA SISWA KELAS V SEKOLAH DASAR - Mariyamah . (Jurnal Education and Development, 2021)
This study aims to describe the increase in interest in learning science on earth structure material through the media of images for fifth grade students of SD Negeri 170 / IX Marga in the second semester of the 2018/2019 academic year. Classroom action research design consisting of 2 cycles, this research is qualitative research. The subjects of this study were students in grade V with a total of 26 students, consisting of 13 female students and 13 male students and the object of this study was the aspects of student interest in learning and the use of image media. The data was collected by using interview techniques, observation (observation), documentation, and field notes. Data analysis used qualitative descriptive analysis techniques through scoring and percentage methods.